Network Architecture of Bidirectional Visible Light Communication and Passive Optical Network - Chi-Wai Chow; Chien-Hung Yeh; Yang Liu; Chin-Wei Hsu; Jiun-Yu Sung (IEEE Photonics Journal, 2016)
Network architectures to combine the fiber network outside the building and the visible light communication (VLC) access network inside the building are important for effectively distributing the high-capacity data to different users. In this paper, we propose a bidirectional network combining the VLC access network and the time–wavelength-division-multiplexed passive optical network (TWDM-PON). Orthogonal frequency division multiplexed modulation is used since it offers high spectral efficiency for both the TWDM-PON and the VLC access network. Low-cost phosphor-based white-light light-emitting diodes are (LEDs) used; hence, the VLC access network can combine with the lighting systems.